Comparative Analysis of Effects of Different Raw Materials on Flavour Quality of Scallion Oil Based on HS-SPME-GC-MS - Meng ZHANG; Peng WANG; Jingzhang GENG; Ping ZHAN; Honglei TIAN (Shipin gongye ke-ji)
To explore the impact of different varieties of scallions on the aromatic profile of fried scallion oil, three commercially available scallion types were utilized as raw materials. Peanut oil served as the carrier fat, and the scallions were finely chopped and fried at 130 ℃ for 3 min to yield samples of scallion-flavored oil, denoted as fried Dacong oil (DFO), fried Hongcong oil (HFO), and fried Xiaocong oil (XFO). Quantitative descriptive sensory analysis (QDA) and headspace solid-phase microextraction-gas chromatography-mass spectrometry (HS-SPME-GC-MS) techniques were employed to examine and analyse the volatile composition among the samples. Furthermore, multivariate statistical analysis was conducted to identify key compounds contributing to variations in sensory attributes among the three types of scallion oils. The sensory evaluation results revealed that XFO displayed pronounced shallot aroma and fat flavor, coupled with high intensity and low levels of oiliness and pungency compared to scallion oil samples prepared under identical process parameters. A total of 66 substances were identified by GC-MS, and 18 key substances were pinpointed through orthogonal partial least squares analysis (OPLS-DA), elucidating the disparities in aroma profiles among the three scallion oils. Relative odor activity value (ROAV) analysis highlighted specific compounds, including 2-ethyl-6-methylpyrazine, propionaldehyde, 2,6-diethylpyrazine, benzaldehyde, guaiacol, benzyl alcohol, 5-methylfurfural, 2-acetylpyrazine, 2-pentylfuran, 3-ethyl-2,5-dimethyl-pyrazine, (E)-2-octenal, 2-pyrrolecarboxaldehyde, N-methyl-2-pyrrolecarboxaldehyde, and 2,3,5-trimethylpyrazine as primary contributors to the distinct flavor profiles observed in the scallion-flavored oil samples. Notably, XFO garnered preference from the panelists relative to the other two scallion oils, aligning with the anticipated aroma profile of scallion oils. This study employed HS-SPME-GC-MS to discern distinct compounds associated with scallion oil, thereby laying a theoretical groundwork for standardized processing methods conducive to producing high-quality scallion oil in subsequent endeavors.